ABHW: Federal court overstepped bounds in rejecting insurer guidelines in Wit. Issue 17 (1st May 2021) - Enos, Gary
Abstract : The national association representing managed behavioral health care companies has formally weighed in on the appeal of the landmark Wit v. United Behavioral Health court ruling, arguing in a filing that the U.S. District Court overstepped its authority in ruling that UBH's coverage guidelines were contrary to generally accepted standards of care.